Believing and seeing: the art of Gothic cathedrals - Recht, Roland (Univ. of Chicago Press, 2008)
Gothic architecture: technology and symbolism -- Ornament, style, and space -- The seen and the unseen -- Architecture and the "connoisseurs" -- The carved image and its functions -- Models, transmission of forms and types, and working methods